Model Evaluasi CIPP: Analisis kebijakan Permendikbud No. 30 Tahun 2017 tentang Pelibatan Keluarga Pada Penyelenggaraan Pendidikan pada Satuan PAUD - Amalia Husna; Rosa Ria Ayu (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2022)
Parents are the first home and environment for children. Given the importance of the role of the family in children's education, the government issued a policy in Permendikbud No. 30 of 2017 concerning Family Involvement in the Implementation of Education in PAUD units. Therefore, it is necessary to evaluate the implementation of every policy made. With the implementation evaluation, we can assess how the implementation process has been so far and what needs improvement and maintenance. This research is qualitative research. In this qualitative research, a literature study was conducted by examining various existing literature from print media and the internet. In addition, the research was conducted by evaluating policies with the CIPP evaluation model. The research result showed that Permendikbud No.30 2017 have been implemented on input, process and product contextually and execellent.